Predicting Project Outcomes : A Simple Methodology for Predictions Based on Project Ratings - Blanc, Marc; Esmail, Talib; Mascarell, Caroline; Rodriguez, Rukshan (World Bank, Washington, DC, 2016)
The downgrading of projects at the closing from moderately satisfactory to moderately unsatisfactory has been a persistent problem in the World Bank and a particular problem in the World Bank's East Asia and Pacific region since 2012. Through analysis of the projects that exited the East Asia and Pacific region's portfolio in fiscal years 2012 and 2013, this paper derives a prediction model based on ratings for implementation progress and achievement of development objectives during project supervision. The model, used in combination with other indicators of project progress toward outcomes, appears to improve on existing methods for assessing the downgrade risk.